Challenges to Peruvian Education in XXIst Century - Arturo Mario Rojas Huerta (Universidad Autónoma de Madrid, 2016)
The new educational trends and the needs of the use of new educational technologies in the curriculum and teaching practices, the Peruvian schools must adapt to these changes so that the future citizens give effective responses to the characteristics and demands of current society and leave behind the nineteenth century that still prevails in Peruvian schools. So this paper analyzes the most relevant characteristics of the knowledge society, the relation between the school and the characteristics of this society, the teacher education and the role of teachers and at the end it mentions what school is required to respond to this demand that today's society, and in which the education faculties of universities have a major role.